Thermal and Concentration Analysis of Mucociliary Johnson-Segalman Fluid Flow in Chronic Obstructive Pulmonary Disease (European Journal of Pure and Applied Mathematics, 2025)
Analyzing mucociliary transport’s thermal and concentration aspects is crucial for comprehending mucus hypersecretion mechanisms in chronic obstructive pulmonary disease (COPD). The present paper uses a mathematical model of two-layered fluid flow in a finite two-dimensional airway channel. This model uses the hypersecretion scenario, where goblet cells secreted mucus in large volume, leading to complete blockage of the airway channel as the airway ciliary layer (ACL) and peri ciliary layer (PCL). Johnson-Segalman fluid model is used to characterize secreted mucus. The analysis delineated that temperature rises with increasing conductivity ratio, pressure gradient at the airway channel entrance, and Weissenberg number of PCL, while concentration decreases with increasing pressure gradient at the airway channel entrance and Weissenberg numbers. The analysis also highlights the impact of high Weissenberg numbers on mucus velocity. Johnson-Segalman fluid better characterizes secreted mucus as it improves mucus clearance in the respiratory system, particularly in patients with severe COPD.
Keywords: Mucus hypersecretion, ciliary cells, thermal and concentration, Johnson-Segalman fluid, two-layered model